Glycemic Control among Type-2 Diabetes Mellitus Patients: A Large Samples Hospital Based Study (Medical Forum Monthly, 2020)
Objective: To find out the sugar control among type 2 diabetic patients assessed on glycosylated hemoglobin (HbA1C) test.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at the Pathology Department, Kuwait Teaching Hospital, Peshawar from January 2017 to December 2018.Materials and Methods: A total of 2654 participants were in the study. The inclusion criteria were type 2 diabetic cases, Pakistani nationals, both genders, and age above 18 years. Freshly diagnosed type 2 diabetes, secondary diabetes, type 1 diabetes, pregnancy associated diabetes, unknown type of diabetic cases or endocrine disorders were excluded. The recorded data were age, gender, and HbA1C.Poor glycemic patients were those cases having above 7% HbA1C level.Results: The mean age of the participants of the study was 51.96±13.84 years and mean glycosylated hemoglobin 8.52±3.060. The females (n=1608, 60.6%) were more than males (n=1046, 39.4%). Of total sample 2654 the poor glycemic control (>7% HbA1C) was in 1705(64.2%) participants while in 949(35.8%) the glycemic control was good (<7% HbA1C). Glycemic control was different among the age groups very highly statistically significantly (P<0.001). With increasing age the glycemic control become poorer.Conclusion: About two third type 2 diabetic patients have poor sugar control in our population. These results should be considered in future interventional research aiming to improve glycemic control in type 2 diabetes mellitus patients.